The quality of dietary intake methodology and reporting in child and adolescent obesity intervention trials: a systematic review - Burrows, Tracy; Golley, Rebecca K.; Khambalia, Amina; McNaughton, Sarah A.; Magarey, Anthea; Rosenkranz, Richard R.; Alllman-Farinelli, Margaret; Rangan, Anna M.; Truby, Helen; Collins, Clare (My University, 2012)
Background: Assessing dietary intake is important in evaluating childhood obesity intervention effectiveness. Purpose: To evaluate the dietary intake methods and reporting in intervention studies that included a dietary component to treat overweight or obese children. Methods: A systematic review of studies published in the English language, between 1985 and August 2010 in health databases. Results: The search identified 2295 papers, of which 335 were retrieved and 31 met the inclusion criteria. Twenty-three studies reported energy intake as an outcome measure, 20 reported macronutrient intakes and 10 studies reported food intake outcomes. The most common dietary method employed was the food diary (n=13), followed by 24-hour recall (n=5), food frequency questionnaire (FFQ) (n=4) and, dietary questionnaire (n=4). The quality of the dietary intake methods reporting was rated as ‘poor’ in 15 studies (52%) and only three were rated as ‘excellent.’ The reporting quality of FFQs tended to be higher than food diaries/recalls. Conclusions: Deficiencies in the quality of dietary intake methods reporting in child obesity studies were identified. Use of a dietary intake methods reporting checklist is recommended. This will enable the quality of dietary intake results to be evaluated, and an increased ability to replicate study methodology by other researchers.
Keywords: Diet; Nutrition; Obesity; Overweight; Children; Interventions